Principal Management in Improving Teacher Quality at State Vocational High School - Cut Wan Moulida; Yusrizal Yusrizal; Niswanto Niswanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to collect empirical data regarding the effectiveness of academic supervision in enhancing teacher professionalism at Lhokseumawe State Vocational High School. Academic supervision must be data-driven and factually accurate. Academic supervision is everyday work that supervisors must perform in order to meet the needs of a dynamic curriculum that is constantly in need of improvement in terms of documentation and context in the field. This research employs a qualitative approach combined with descriptive analysis techniques. The primary data sources for this study were direct interviews with informants, including school principals, teachers, students, observations, and secondary materials culled from various studies of papers, texts, and archives about Academic Supervision implementation. According to the researcher's analysis, the principal has utilized academic supervision to enhance teacher professionalism, as evidenced by the planning of supervision schedules, implementation, assessment of teacher performance using prepared learning instruments, and follow-up on the results of learning supervision. The supervision theory has been implemented effectively, including directing supervision in learning and the conduct of pre-supervision meetings with teacher interviews.